Properties of Escherichia coli mutants altered in calcium/proton antiport activity. - Brey, R N (1979)
Mutants sensitive to growth inhibition by CaCl2 were found to have alterations in calcium uptake in everted membrane vesicles. These mutations map at different loci on the Escherichia coli chromosomes. A mutation at the calA locus results in vesicles which have two- to threefold higher levels of uptake activity than vesicles from wild-type cells. The calA mutation is phenotypically expressed as increased sensitivity to CaCl2 in a strain also harboring a mutation in the corA locus, which is involved in Mg2+ transport. The calA locus maps very close to purA and cycA at about min 97. The calB mutation results both in sensitivity to CaCl2 at pH 5.6 and in vesicles with diminished calcium transport capability. The CalB phenotype is also expressed only in a corA genetic background; the calB locus appears to map very near, yet separately from, the calA locus. When the cor+ allele is present, calA and calB mutations still result in a defect in calcium transport in vesicles. In addition, both calC and calD mutations result in vesicles with impaired calcium transport activity. calC is cotransducible with kdp and nagA, whereas calD is cotransducible with proC.